Proinsulin: from hormonal precursor to neuroprotective factor - De Pablo, Flora; de la Rosa, Enrique J. (Frontiers in Molecular Neuroscience, 2011)
In the last decade, non-canonical functions have been described for several molecules with hormone-like activities in different stages of vertebrate development. Since its purification in the 1960s, proinsulin has been one of the best described hormonal precursors, though it has been overwhelmingly studied in the context of insulin, the mature protein secreted by the pancreas. Beginning with our discovery of the presence and precise regulation of proinsulin mRNA in early neurulation and neurogenesis, we uncovered a role for proinsulin in cell survival in the developing nervous system. We subsequently demonstrated the ability of proinsulin to prevent pathological cell death and delay photoreceptor degeneration in a mouse model of retinitis pigmentosa. In this review, we focus on the evolution of proinsulin/insulin, beginning with insulin-like peptides expressed in mainly the neurosecretory cells of some invertebrates. We summarize findings related to the regulation of proinsulin expression during development and discuss the possible effects of proinsulin in neural cells or tissue, and its potential as a neuroprotective molecule.